Pertemuan Kepala Daerah Melalui Pendekatan Collaborative Governance dalam Upaya Pengendalian Produk Tembakau di Indonesia Timur - Ismi, Ismi; Handayani, Meliana; Wadi, Ahmad; Hasyim, Hadijah; Jayadilaga, Yadi; Isnaeni, Nur Fajri Tika; Sari, Nur Indah (Program Studi Manajemen FEB UNM, 2026)
The high prevalence of smoking and second-hand smoke exposure in Indonesia, particularly in Eastern Indonesia, underscores the need to strengthen political commitment and accelerate the implementation of Smoke-Free Area (SFA) policies at the subnational level. This community service program aimed to enhance inter-regional collaboration among local government leaders through a collaborative governance approach to tobacco control. The activity was conducted during the Eastern Indonesia Mayor Meeting Forum on April 23–24, 2024, in Makassar, involving 14 mayors/regency representatives, national government officials, academics, and tobacco control advocacy organizations. The implementation followed a four-stage collaborative governance framework: starting conditions, facilitative leadership, institutional design, and face-to-face collaborative processes. The forum successfully facilitated multi-stakeholder dialogue and produced five strategic agreements aimed at reducing the number of new smokers and minimizing exposure to second-hand smoke. These agreements were formalized in a Joint Commitment Letter, reflecting strengthened political commitment at the local level. The forum also enhanced knowledge exchange, inter-regional networking, and both vertical and horizontal coordination mechanisms. Overall, this collaborative approach contributed to strengthening local capacity and political commitment in implementing SFA policies and holds potential to accelerate tobacco control policy diffusion across Eastern Indonesia.